Optimization of land use at Mt. Yuelu scenic area: an analysis using the ecological green equivalent - Xi Chen; Ke-lin Wang; Wei-jun Zhou; Hong-bin Li; Muhammad Aqeel Ashraf (Earth Sciences Research Journal)
This study applies the ecological green equivalent approach to evaluating the land use structure of Mt. Yuelu scenic area in Hunan Province, China. A mathematical model is established based on land use and land cover data, and then ArcGIS used to extract the spatial extent of the ecological green equivalent within each of the relevant elements. Results show that the area has a relatively reasonable land use structure even though the forest coverage rate is slight below the optimum. The overall green equivalent (1.13) was higher than the optimum forest coverage ecological green equivalent (1.00). The distribution of forest was uneven, with most of the forest within the site; the area’s land use structure could thus be improved by extending the green area outside of Mt. Yuelu. We conclude by reiterating that landscape and infrastructure development should consider ecological system conditions.